2018
DOI: 10.9734/jamb/2018/41007
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Pattern and Plasmid Profile of E. coli Isolated from Diarrhoeic Children in Selected Health Centres in Sokoto, Nigeria

Abstract: Methodology: A total of 236 stool samples were collected from diarrhoeic children of age ≤5 years from selected Hospitals in Sokoto, Nigeria. Isolation and identification of E. coli strains were carried out using standard methods and procedures. Antibiotic susceptibility testing was performed using disc-diffusion method. Plasmid extraction was carried out using alkaline lysis method while curing of the plasmid harbouring strains was done using standard curing technique. Results: The result showed that 96 (41%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Results of this research show that a high degree of ceftazidime resistance in the test isolates was plasmid mediated. Similar to this study, two other studies involving plasmid curing had reported that highest levels of change in resistance occurred in ceftazidime specifically or cephalosporins in general (Awopeju et al, 2015, Alkali et al, 2018, Orhue et al, 2017. Plasmid curing had less of an effect on levels of resistance (25% change) against cefuroxime which is a 2nd generation cephalosporin than ceftazidime.…”
Section: Discussionsupporting
confidence: 84%
“…Results of this research show that a high degree of ceftazidime resistance in the test isolates was plasmid mediated. Similar to this study, two other studies involving plasmid curing had reported that highest levels of change in resistance occurred in ceftazidime specifically or cephalosporins in general (Awopeju et al, 2015, Alkali et al, 2018, Orhue et al, 2017. Plasmid curing had less of an effect on levels of resistance (25% change) against cefuroxime which is a 2nd generation cephalosporin than ceftazidime.…”
Section: Discussionsupporting
confidence: 84%